Co-management—An Attainable Partnership? Two Cases from James Bay, Northern Quebec and Torres Strait, Northern Queensland - Mulrennan, M.E.; Scott, C.H. (Anthropologica, 2022)
Two case studies of indigenous peoples engaged in resource co-management arrangements—James Bay Crees and Torres Strait Islanders—support three arguments. First, co-management involving true power-sharing with central governments is very different from "co-management," so-called, that offers mere advisory status (though the latter may sometimes be developed into the former). Second, power-sharing by the state depends on sustained political action by indigenous people demonstrating that there are real costs to the state, or interests influential with the state, in ignoring indigenous demands and priorities. Finally, the degree to which indigenous knowledge and institutions shape co-management practice is directly related to the power of the indigenous people involved.